Feasibility Analysis Of Sharia-Based Local Productive Enterprises In Phatnawitya School Yala, Thailand - Dwiyana, Anisyah Kesuma; Syahrul Amsari (University of Darussalam Gontor, 2024)
The community around Phatnawitya Yala School has a variety of local potentials that include agriculture, fisheries, handicrafts, and service sectors. This region is known as one of the high-quality rice-producing areas, with an agricultural system that is still traditional but has the potential to be developed into a modern agribusiness. This research analyzes the feasibility of sharia-based local businesses in the Pahtna Witya Yala School community in Thailand